Protection with Steel Corrosion Inhibitors in Hydrogen Sulfide Environments - K. P. Norbutaeva (Genius Journals, 2022)
Ensuring the reliability and durability of equipment and pipeline systems is one of the most important tasks in the development of oil and gas fields and in the further transportation and processing of hydrocarbons. Corrosion of steel equipment and pipelines, in addition to reducing their service life and increasing the cost of their repair, can cause serious damage to the environment. The article considers the literature data on inhibitors of hydrogen sulfide corrosion of carbon steel, including those recommended for use in similar conditions abroad.
Keywords: Corrosion; protection; inhibitor; hydrogen sulfide